PERTAUTAN ANTARA ASPEK INTELEKTUAL DAN MISTIS DALAM NOVEL LANANG KARYA YONATHAN RAHARDJO - Sugiarti, Sugiarti (LITERA, 2014)
This study aims to describe the connection between the intellectual and mystical aspects in Lanang, a novel by Yonathan Rahardjo. It employed the qualitative phenomenological approach using principles in qualitative content analysis to understand text messages descriptively. The data sources were Lanang and the results of interviews with the author. The data comprised the story sequence relevant to the research objectives and important information obtained from literature review. The findings are as follows. First, the intellectual aspect stimulates awareness that the technology sophistication is capable of changing what is impossible into what is possible, such as animal biotechnology engineering. Second, the mystical aspect originates from beliefs in a local tradition that may be illogical and full of weirdness but people still believe them.